Road Pavement Condition Index as a Method to Analyze the Level of Road Damage - Falakush Shobah Almubarok; Rachmat Mudiyono; Soedarsono S (Universitas Islam Sultan Agung, 2022)
The pavement Condition Index (PCI) method serves to measure the severity of pavement damage based on 3 main categories: (1) type of damage, (2) severity of damage, and (3) amount or density of damage. PCI is a numerical index whose values range from 0 to 100. A value of 0 indicates the pavement was in very damaged condition, while a value of 100 indicates that the pavement was still excellent. A survey was conducted on Jalan Tregguli - Welahan along ± 1 km divided into several segments to identify road damage. Each segment was 100 m apart. PCI for Trengguli - Welahan road segment which belonged to 0 – 10 (failed) of 0%, 11 – 25 (very bad) of 11%, 26 – 40 (bad) of 28%, 41 – 55 (moderate) of 8%, 56 – 70 (good) of 12%, 71 – 85 (very good) of 19%, and 86 – 100 (Perfect) of 22%, The average PCI for Trengguli Welahan road segment is of 54.36. The findings classified road damages into road patches, longitudinal/transverse cracks, holes, and joint cracks. The PCI value is 54.36 (medium). Based on data on the PCI value and the percentage of damage on the road of Trengguli - Welahan, there is a high correlation between the two variables.